Application of Biostimulants in Tomato Plants (Solanum lycopersicum) to Enhance Plant Growth and Salt Stress Tolerance - Gedeon, Stella; Ioannou, Andreas; Balestrini, Raffaella; Fotopoulos, Vasileios; Antoniou, Chrystalla (My University, 2022)
Under the era of climate change, plants are forced to survive under increasingly adverse conditions. Application of biostimulants in plants is shown to mitigate the deleterious effects of abiotic stresses including salinity, enhancing plant tolerance and performance. The present study focuses on the effects of five biostimulants based on biocompost and biofertilizer compounds that have been applied to tomato plants grown in the presence (salt-stressed plants) or absence of salt stress (control plants). To study the beneficial effects of the biostimulants in tomato plants, a series of analyses were performed, including phenotypic and agronomic observations, physiological, biochemical and enzymatic activity measurements, as well as gene expression analysis (RT-qPCR) including genes involved in antioxidant defense (SlCu/ZnSOD, SlFeSOD, SlCAT1, SlcAPX), nitrogen (SlNR, SlNiR, SlGTS1) and proline metabolism (p5CS), potassium transporters (HKT1.1, HKT1.2), and stress-inducible TFs (SlWRKY8, SlWRKY31). Among all the biostimulant solutions applied to the plants, the composition of 70% biofertilizer and 30% biocompost (Bf70/Bc30) as well as 70% biocompost and 30% biofertilizer (Bc70/Bf30) formulations garnered interest, since the former showed growth promoting features while the latter displayed better defense responses at the time of harvesting compared with the other treatments and controls. Taken together, current findings provide new insight into the beneficial effects of biostimulants, encouraging future field studies to further evaluate the biostimulant effects in plants under a real environment which is compromised by a combination of abiotic and biotic stresses.
Keywords: Abiotic stress; Growth promotion; Priming; Salinity; Tomato